1998
DOI: 10.1002/(sici)1097-4636(19980615)40:4<530::aid-jbm3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Repassivation of titanium and surface oxide film regenerated in simulated bioliquid

Abstract: The change in potential during repassivation of titanium in artificial bioliquids was examined, and the regenerated surface oxide film on titanium was characterized using X-ray photoelectron spectroscopy and Auger electron spectroscopy to elucidate the repassivation reaction of titanium in a biological system. The repassivation rate in Hanks' solution was slower than that in saline and was not influenced by the pH of the solution. This indicates that more titanium ions dissolve in a biological system than hith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(80 citation statements)
references
References 31 publications
(39 reference statements)
0
80
0
Order By: Relevance
“…27) On the other hand, the Ti 2p spectrum gave four doublets according to valence: Ti 0 , Ti 2+ , Ti 3+ , and Ti 4+ . 14) Published data 28,29) were used for the binding energy of each valence titanium. The decomposition spectrum shows that Ti 2+ oxide exists inside the surface oxide layer; nevertheless, Ti 2+ formation is always thermodynamically less favorable than Ti 3+ formation at the surface.…”
Section: Ti-6al-4v Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…27) On the other hand, the Ti 2p spectrum gave four doublets according to valence: Ti 0 , Ti 2+ , Ti 3+ , and Ti 4+ . 14) Published data 28,29) were used for the binding energy of each valence titanium. The decomposition spectrum shows that Ti 2+ oxide exists inside the surface oxide layer; nevertheless, Ti 2+ formation is always thermodynamically less favorable than Ti 3+ formation at the surface.…”
Section: Ti-6al-4v Alloymentioning
confidence: 99%
“…14) The pH of the solution does not influence the repassivation rate within the pH range examined. These results indicate that the repassivation of titanium in biological systems is slower than hitherto predicted when the surface oxide film is destroyed, possibly inducing the dissolution of more titanium ions into bioliquid.…”
Section: Introductionmentioning
confidence: 96%
“…The passive films of these materials allow them to maintain resistance to corrosion [1][2][3] . Although titanium and its alloys are well-known for their good corrosion resistance in the body, titanium appliances do occasionally show discoloration or corrosion in an oral environment 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…4 The induction of corrosion resistance and cytocompatibility is related to the presence of an oxide (passive) layer that prevents the formation of fibrous tissue around the implant and creates direct contact to the bone tissue. Hanawa et al 5,6 have shown that presence of oxide layer also has a significant effect Ca/P ratio in the calcium phosphate (close to hydroxyapatite a bone material) film compared to pure titanium alloy during mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…The dual character of the oxide film, i.e., the presence of areas covered by an aluminum oxide film on Ti6Al4V may have caused the changes in the Ca/P ratio. 5,6,10 It is thus important to understand how the changes in surface composition, for example, by the local surface presence of Al-rich and V-rich oxides (in a matrix of TiO 2 ) influence cell adhesion and development and if this can be traced back to local contrast in protein adsorption. However, since the surface chemistry cannot be completely dissociated from the surface topography and energy, all of these need to be studied concomitantly.…”
Section: Introductionmentioning
confidence: 99%